THE EFFECTS OF SINGLE CELL PROTEIN ON AL-AWASSI LAMBS IN IRAQ - S. Mohmoud, Ghyath; M.Z. Al-Kinnani , Layla; F. Hasson‎, Abbas (The Iraqi Journal of Veterinary Medicine, 1987)
The effects of single cell protein (SCP) were studied in Al-Awassi lambs in Iraq. Four groups of lambs received 0%, 5%, 10% and 15% of (SCP) as a replacer for a soybean. The influence of (SCP) on the performance and carcass data of lambs and their blood pictures were studied. The total uric acid, blood urea and the histopathological changes were also investigated. The results - showed” that ‘there were no significant (P>0.05) differences ‘among the initial, slaughtered, total weights gained and chilled carcass weights. The wholesale cuts showed. no significant (P>0.05) differences. The eye rib area, fat thickness of. longissmus doris muscle, average percentage of organs and offal dressing percentage (calculated in live and empty body weight basis) were similar in all groups examined. the blood and serum parameters did not differ significantly (P>0.05) among the experimental groups.